Toneta Pretnarja prevod sonetov Jana Nepomucena Kamińskega - Šurla, Andrej (Jezik in slovstvo, 2017)
In the first half of the nineteenth century, Jan Nepomucan Kamiński was an important figure in Polish cultural life in Lvov. He is, however, less known as a poet. Tone Pretnar's decision to translate fourteen of Kamiński's sonnets into Slovene came about primarily due to his personal links with Matija Čop. His translations are probably aesthetically more powerful than the original; they are marked by a subtle and refined use of elements of the language of France Prešeren, whereby the translator succeeds in instilling into his rendering in the Slovenian language a sense of the era and the meta-literary environment in which the sonnets came into being in their original form.
Keywords: Pretnar, Tone, 1945-1992; Kamiński, Jan Nepomucen, 1777-1855; Polish literature; poljska književnost; poljski pesniki; prevodi v slovenščino; literarni prevod; prešernizmi; sonet